Development of the conceptual framework for soil protection and management in the European Union - A. L. Ivanov; V. S. Stolbovoy; A. M. Grebennikov (Бюллетень Почвенного института им. В.В. Докучаева, 2022)
The concepts defining the policy of soil protection and rational use (SPRU) in the European Union (EU) are considered. It is found that the focuses of SPRU have evolved significantly since the early 1990s. Initially the SPRU was not considered separately, it was associated with the protection of other environment components, for example, soil соntamination resulting from air pollution or the disposal of industrial and municipal wastes. In 2006 the stand-alone EU Soil Protection Strategy was established. This document was focused on soil protection against physical degradation (erosion, compaction, sealing, etc.) and on preservation of soil functions. The new Soil Strategy 2030 is based on the provisions of the previous Strategy document and is primarily aimed at improving soil health. Special attention is paid to the conservation of soils as a spatial resource and its efficient use in the system of a circular (closed-loop economy) economy. Looking at the evolution of the EU policy towards the SPRU, it can be concluded that the main development has led to an understanding of the importance of soil health and awareness of the need to conserve soil as multi-target spatial and functional basis for human health, wildlife and climate.